Preexisting cognitive impairment in patients with acute stroke - Kassir, Sarah; Béjot, Yannick (Frontiers in Neurology, 2025)
Preexisting cognitive impairment is a significant but often overlooked factor in the management and outcome of stroke patients. Patients with prior cognitive impairment suffering a stroke have less access to stroke units, and less administration of acute revascularization therapies, as a possible consequence of limited research on the benefits of these treatments in this specific population, with most data coming from observational studies. Prestroke cognitive impairment is associated with a greater clinical severity at onset, increased complications, and poorer survival and functional outcome, with a reduced access to rehabilitation services, and a greater need for institutionalization. Patients with preexisting cognitive impairment have more prevalent comorbidities and frailty, which contribute to their increased vulnerability to adverse health outcomes. Further research is needed to better understand how these factors may influence clinical outcomes and decision-making in stroke care in patients with neurocognitive disorders. More inclusive clinical trials and standardized assessment strategies to guide optimal care for this vulnerable population are required. This will be crucial in adapting healthcare systems to meet the needs of a growing and aging population.